The Effects of Motivation and Competency on Human Resources Performance of Program Keluarga Harapan (Family Hope Program) in Banyuasin District - Afriliana, Nadia; Sudarta, Sudarta; Mawarni, Mentari Vieka (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
Motivation and competence are closely related to performance. Motivation and competence felt directly by the Family Hope Program's human resources program can reduce performance or increase the performance of the Family Hope Program. This research is conducted on the Family Hope Program in Banyuasin District. This study aimed to determine the effect of motivation, competence jointly and partially on human resources performance of the hope family program in Banyuasin District. The variables in this study were motivation and competence in performance. The population in this study was 133 human resources of The Family Hope Program in Banyuasin District with 57 samples. The sampling technique in this research was Simple Random Sampling. The results of data analysis in this study showed that together motivation and competence variables had a significant effect on the human resources performance of the Family Hope Program in Banyuasin District. Individually, the motivation variable has a significant impact on performance. The competency variable did not significantly affect performance, and the competency variable significantly affected the human resources performance of the Family Hope Program in Banyuasin District